The phenotypic characteristics and morphology of Jabres and Pasundan cattle differences - YOYO SURYAKA; SUTOPO SUTOPO; ASEP SETIAJI (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Suryaka Y, Sutopo S, Setiaji A. 2024. The phenotypic characteristics and morphology of Jabres and Pasundan cattle differences. Biodiversitas 25: 3239-3246. Pasundan and Jabres cattle, prominent Indonesian breeds, exhibit unique phenotypic characteristics crucial for sustainable breeding and conservation. This study, aimed at delineating phenotypic differences between Pasundan and Jabres cattle, two prominent Indonesian breeds, is a hope for the country's sustainable breeding and conservation efforts. Data were collected from 131 adult cattle (71 Pasundan, 60 Jabres) from Kuningan and Brebes Districts, spanning July 2022 to June 2023. Morphological and morphometric analyses highlighted key distinctions: Pasundan cattle predominantly feature a solid reddish-brown coat, while Jabres cattle exhibit more diverse colors, including black. Jabres cattle showed significantly greater body length and chest girth than Pasundan cattle. Canonical Discriminant Analysis (CDA) effectively distinguished the breeds, especially in females, with 83.33% accuracy for Pasundan and 79.31% for Jabres. Critical discriminant traits included chest width and rump length. The findings suggest that Pasundan and Jabres cattle possess unique phenotypic traits driven by genetic, environmental, and management factors. These insights are crucial for developing targeted breeding strategies to enhance breed-specific characteristics, laying the groundwork for a promising future for Indonesia's cattle industry.